2009
DOI: 10.1016/j.jtbi.2008.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modelling of fibre-enhanced perfusion inside a tissue-engineering bioreactor

Abstract: We develop a simple mathematical model for forced flow of culture medium through a porous scaffold in a tissue engineering bioreactor. Porous-walled hollow fibres penetrate the scaffold and act as additional sources of culture medium. The model, based on Darcy's law, is used to examine the nutrient and shear stress distributions throughout the scaffold. We consider several configurations of fibres and inlet and outlet pipes. Compared with a numerical solution of the full Navier-Stokes equations within the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…It is crucial that lactate is eliminated from the construct before this critical concentration l * is reached. In [50], the authors estimate the concentration of lactic acid that would be harmful to the growing cells for a buffered culture medium. It is assumed that growing cells can tolerate a pH change of up to ±0.5, and titration experiments indicated that the harmful concentration of lactic acid in a buffered medium was ≈ 0.4 mol m −3 .…”
Section: Dimensional Analysismentioning
confidence: 99%
“…It is crucial that lactate is eliminated from the construct before this critical concentration l * is reached. In [50], the authors estimate the concentration of lactic acid that would be harmful to the growing cells for a buffered culture medium. It is assumed that growing cells can tolerate a pH change of up to ±0.5, and titration experiments indicated that the harmful concentration of lactic acid in a buffered medium was ≈ 0.4 mol m −3 .…”
Section: Dimensional Analysismentioning
confidence: 99%
“…K p is the permeability value of the porous media that is calculated in Eq. . Knormalp=ɛ·δ2160Where δ is the pore size of the scaffold.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, numerical evaluation provides insight into local hydrodynamic changes in tissue constructs in order to generate quantitative anticipation of the tissue development within a bioreactor system [116]. Finally, with the aid of recently available computational tools, variables (e.g., flow fields of a particular bioreactor design [117, 118], incorporation of the mechanics of the scaffold material [119], and the sufficiency of bioreactor cultures [117, 120, 121], shear stresses and mass transfer in scaffold-containing bioreactors [118, 122]) can be estimated.…”
Section: Mathematical Modeling Of Engineering Parametersmentioning
confidence: 99%